Dinâmica de grafoelementos do sono e seus impactos na neurofisiologia de pacientes com apneia obstrutiva através de sinais de eletroencefalografia - Souza, Rafael Toledo Fernandes de [UNESP] (2016)
Sleep (derived from the Latim, somnus) is a brain state with distinct physiological activity that can be investigated by EEG evaluation. Some waves are unique in sleep EEG such as sleep spindles and K complexes. Spindles are one of the best known elements in sleep studies. In this work we considered global spindles and K complexes, which are spindles that are observed simultaneously in all EEG channels. We propose a method that investigates both the signal envelope and phase/frequency of each global spindle. By analysing the spindle phase we showed that 90% of spindles in healthy subjects synchronize with a median latency time of 0.11 s. The method also measured the frequency slope (chirp) of global spindles and found that global spindle chirp and synchronization are not correlated. By investigating the signal envelopes and implementing a homogeneous and isotropic propagation model, we could estimate both the signal origin and velocity in global spindles. Our results indicate that this simple and non-invasive approach could determine with reasonable precision the spindle origin, and allowed us to estimate a signal speed of 0.12 m/s. Potential K complexes are used to assess the robustness of developed method and shows that frequencies, durations and amplitudes within the K complex expected range. Propagation velocity in potential K complexes are around 0.05 m/s which is lower than spindles velocity. Partial synchronization tendencies were detected in potential K complex, a propriety described for K complex in the literature. Obstructive Sleep Apnea (OSA) subjects were also assessed by our method. The majority of analysed parameters do not present significant difference between healthy and OSA subjects except by synchronization duration (34.18% lower in OSA) and two distinct focal points in OSA spindle origin. The proposed methodology retrieved the expected results, obtained by EEG analysis and other more complex techniques and our results indicate that it can be used as a diagnosis tool and to explore other sleep phenomena, such as K complexes.